Listening to Music - Lukač , Nuša (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter outlines the benefits of listening to music for students' holistic development, encompassing emotional, cognitive, and social progress. The focus is on active music listening, which allows pupils to develop a deeper understanding and appreciation of music. The teacher's role is to encourage both spontaneous responses and more detailed analysis of music through musical activities, thereby enhancing the learning experience. Music helps pupils express and understand emotions, improves communication skills, and fosters a sense of belonging and cooperation within a group. Different listening methods, such as the cognitive-emotional approach, further boost learners' motivation and engagement by stimulating more intense emotional responses. Music in the classroom promotes relaxation, connects various learning contents, and supports the development of social skills. As a result, music becomes an indispensable part of the educational process, significantly contributing to the holistic development of pupils.